2014
DOI: 10.2147/copd.s61854
|View full text |Cite
|
Sign up to set email alerts
|

Continuing to Confront COPD International Patient Survey: methods, COPD prevalence, and disease burden in 2012–2013

Abstract: PurposeThe Continuing to Confront COPD International Patient Survey aimed to estimate the prevalence and burden of COPD globally and to update findings from the Confronting COPD International Survey conducted in 1999–2000.Materials and methodsChronic obstructive pulmonary disease (COPD) patients in 12 countries worldwide were identified through systematic screening of population samples. Telephone and face-to-face interviews were conducted between November 2012 and May 2013 using a structured survey that incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
72
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 42 publications
14
72
1
5
Order By: Relevance
“…In each of the age cohorts, more than half of patients had a CAT score ≥10, indicating a high impact of COPD on patients’ HRQoL. This was in line with a population-based survey in Japan that revealed a mean CAT score of 16 points – similar to that observed in this study 35. Earlier studies have shown a strong correlation with the CAT questionnaire with severity of airflow obstruction, dyspnea and comorbidities in Japanese patients 13,36.…”
Section: Discussionsupporting
confidence: 90%
“…In each of the age cohorts, more than half of patients had a CAT score ≥10, indicating a high impact of COPD on patients’ HRQoL. This was in line with a population-based survey in Japan that revealed a mean CAT score of 16 points – similar to that observed in this study 35. Earlier studies have shown a strong correlation with the CAT questionnaire with severity of airflow obstruction, dyspnea and comorbidities in Japanese patients 13,36.…”
Section: Discussionsupporting
confidence: 90%
“…The phenotypic distribution involving both airway and systemic inflammation, in addition to airway obstruction, is similar to that previously described in Western studies 25. A global survey24 also confirmed findings that COPD causes a high societal and personal burden, as demonstrated by high levels of symptoms, poor health status, and high frequency of severe exacerbations of COPD. Given the high prevalence of smoking in Japan, coupled with its aging population, the prevalence of the disease in the country is likely to increase over the next 20–40 years, further increasing the burden of COPD.…”
Section: Epidemiology and Treatment Of Copd In Japansupporting
confidence: 84%
“…A global survey of patients with physician-diagnosed COPD or emphysema or with physician-diagnosed or symptom-based chronic bronchitis reported a prevalence of COPD of 7% in a Japanese population aged 40 years or older 24. The phenotypic distribution involving both airway and systemic inflammation, in addition to airway obstruction, is similar to that previously described in Western studies 25.…”
Section: Epidemiology and Treatment Of Copd In Japansupporting
confidence: 66%
“…At 12 weeks, 24 weeks, 36 weeks, and 52 weeks, a follow-up interview was conducted by telephone, gathering information on productivity losses, health care utilization, and exacerbations of respiratory symptoms. Follow-up by telephone was considered satisfactory as no biological measurements were needed, the interval between interviews was short, and telephone coverage was reliable in the area 32,33. Information on comorbidities was gathered by asking for conditions listed in the Charlson Comorbidity Index 34…”
Section: Methodsmentioning
confidence: 99%